Historical knowledge and the search for truth: a reading of subjectivity and objectivity in the duality between subject and object (Research, Society and Development, 2018)
The present article presents the systematization of theoretical reflections about the debate of neutrality in the human sciences. From the presentation of the conception of scientific neutrality defended by the positivist perspective, a reflection is made on the relation between researcher and object of historical research and its imbrications to the present day. The focus is on the subjective factor and its decisive contribution to research in human science. Thus, the great epistemological richness contained in subjectivity is demonstrated. The methodology used was a bibliographical study, made from researches in classic works of historical science.